2013
DOI: 10.1177/0011128713496007
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Severity Index Scores and Urine Drug Screens at Baseline as Predictors of Graduation From Drug Court

Abstract: Graduation rates from drug courts are impressive and are often attributed to the delivered treatments. However, it is unclear whether graduation rates are bolstered by low severity of drug use problems upon entry into drug court. To address this question, this study examined the relationship between baseline substance use severity and graduation rates among 251 drug court clients. Results revealed that participants with subthreshold drug composite scores on the Addiction Severity Index (ASI) were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This finding is consistent with past literature suggesting the importance of education for drug court completion. Based on the existing literature, having a higher level of education (Brown, 2010;DeVall & Lanier, 2012;Fulkerson et al, 2012;Hartley & Phillips, 2001;Howard, 2016;Shah et al, 2013) has been associated with better drug court program outcomes. Specifically, Shah and colleagues (2013) showed for each additional year of education, the participant was 1.4 times more likely to graduate.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with past literature suggesting the importance of education for drug court completion. Based on the existing literature, having a higher level of education (Brown, 2010;DeVall & Lanier, 2012;Fulkerson et al, 2012;Hartley & Phillips, 2001;Howard, 2016;Shah et al, 2013) has been associated with better drug court program outcomes. Specifically, Shah and colleagues (2013) showed for each additional year of education, the participant was 1.4 times more likely to graduate.…”
Section: Discussionmentioning
confidence: 99%
“…Negative urine screens at baseline are indicative of a good prognosis in treatment overall (Shah et al, 2013; Sofuoglu, Gonzalez, Poling, & Kosten, 2003) and in predominately African American samples as well (Petry, Rash, & Easton, 2011; Tzilos, Rhodes, Ledgerwood, & Greenwald, 2009). However, the current study found differential outcomes in baseline urine results and treatment outcomes by treatment type and race.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with existing literature (Ahmadi et al, 2009), individuals with a negative urine sample at treatment initiation remain in treatment longer and achieve more abstinence than those who enter treatment with a positive sample. Negative urine screens at baseline are indicative of a good prognosis in treatment overall (Shah et al, 2013;Sofuoglu, Gonzalez, Poling, & Kosten, 2003) and in predominately African American samples as well (Petry, Rash, & Easton, 2011;Tzilos, Rhodes, Ledgerwood, & Greenwald, 2009). However, the current study found differential outcomes in baseline urine results and treatment outcomes by treatment type and race.…”
Section: Discussionmentioning
confidence: 45%